Airborne particulate matter and mitochondrial damage: a cross-sectional study - Hou Lifang; Zhu Zhong-Zheng; Zhang Xiao; Nordio Francesco; Bonzini Matteo; Schwartz Joel; Hoxha Mirjam; Dioni Laura; Marinelli Barbara; Pegoraro Valeria; Apostoli Pietro; Bertazzi Pier; et al. (BMC, 2010)
Abstract Background Oxidative stress generation is a primary mechanism mediating the effects of Particulate Matter (PM) on human health. Although mitochondria are both the major intracellular source and target of oxidative stress, the effect of PM on mitochondria has never been evaluated in exposed individuals. Methods In 63 male healthy steel workers from Brescia, Italy, studied between April and May 2006, we evaluated whether exposure to PM was associated with increased mitochondrial DNA copy number (MtDNAcn), an established marker of mitochondria damage and malfunctioning. Relative MtDNAcn (RMtDNAcn) was determined by real-time PCR in blood DNA obtained on the 1st (time 1) and 4th day (time 2) of the same work week. Individual exposures to PM10, PM1, coarse particles (PM10-PM1) and airborne metal components of PM10 (chromium, lead, arsenic, nickel, manganese) were estimated based on measurements in the 11 work areas and time spent by the study subjects in each area. Results RMtDNAcn was higher on the 4th day (mean = 1.31; 95%CI = 1.22 to 1.40) than on the 1st day of the work week (mean = 1.09; 95%CI = 1.00 to 1.17). PM exposure was positively associated with RMtDNAcn on either the 4th (PM10: β = 0.06, 95%CI = -0.06 to 0.17; PM1: β = 0.08, 95%CI = -0.08 to 0.23; coarse: β = 0.06, 95%CI = -0.06 to 0.17) or the 1st day (PM10: β = 0.18, 95%CI = 0.09 to 0.26; PM1: β = 0.23, 95%CI = 0.11 to 0.35; coarse: β = 0.17, 95%CI = 0.09 to 0.26). Metal concentrations were not associated with RMtDNAcn. Conclusions PM exposure is associated with damaged mitochondria, as reflected in increased MtDNAcn. Damaged mitochondria may intensify oxidative-stress production and effects.